Identification of Self Disclosure Levels among Students Addicted to Online Games at a Senior High School in Muaro Jambi - Fadila, Nur; Sofyan, Hendra; Yusra, Affan (The Future of Education Journal, 2026)
This research is motivated by the increasing use of online games among adolescents, which has the potential to affect interpersonal communication skills, particularly self-disclosure. This study aims to identify the level of self-disclosure in students addicted to online games at SMA Negeri 11 Muaro Jambi based on the dimensions of amount, valence, honesty and accuracy, intention, and intimacy. This study used a quantitative approach with descriptive methods. The research sample consisted of 60 students determined through a total sampling technique with the criteria of playing online games for more than 5 hours per day. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability and was compiled based on Devito's self disclosure theory and analyzed using a percentage technique. The results showed that the overall level of student self-disclosure was in the high category (61%). Partially, the amount dimension was in the moderate category (59%), while valence (60%), honesty and accuracy (63%), intention (64%), and intimacy (61%) were in the high category. The intention dimension was the highest, while amount was the lowest. These findings indicate that students addicted to online games have a tendency to be quite open, but not optimal in the frequency and duration of self-disclosure. Therefore, guidance and counseling services are needed to increase self disclosure and control online game use to support students' social development.